Linkage and association analysis of candidate genes for TB and TNFa cytokine expression: evidence for association with IFNGR1, IL-10, and TNF receptor 1 genes - Stein, Catherine M.; Zalwango, Sarah; Chiunda, Allan B.; Millard, Christopher; Leontiev, Dmitry V.; Horvath, Amanda L.; Cartier, Kevin C.; Chervenak, Keith; Boom, W. Henry; Elston, Robert C.; Mugerwa, Roy D.; Whalen, Christopher C.; et al. (Springer, 2007)
Tuberculosis (TB) is a growing public health threat globally and several studies suggest a role of host genetic susceptibility in increased TB risk. As part of a household contact study in Kampala, Uganda, we have taken a unique approach to the study of genetic susceptibility to TB by developing an intermediate phenotype model for TB susceptibility, analyzing levels of tumor necrosis factor-a (TNFa) in response to culture filtrate as the phenotype. In the present study, we analyzed candidate genes related to TNFa regulation and found that interleukin (IL)-10, interferon-gamma receptor 1 (IFNGR1), and TNFa receptor 1 (TNFR1) genes were linked and associated to both TB and TNFa. We also show that these associations are with progression to active disease and not susceptibility to latent infection. This is the first report of an association between TB and TNFR1 in a human population and our findings for IL-10 and IFNGR1 replicate previous findings. By observing pleiotropic effects on both phenotypes, we show construct validity of our intermediate phenotype model, which enables the characterization of the role of these genetic polymorphisms on TB pathogenesis. This study further illustrates the utility of such a model for disentangling complex traits.
Keywords: Genes; TNFa cytokine